2016
DOI: 10.1186/s12864-016-3200-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome profiling of two Brassica napus cultivars under chromium toxicity and its alleviation by reduced glutathione

Abstract: BackgroundChromium (Cr) being multifarious industrial used element, is considered a potential environmental threat. Cr found to be a prospective water and soil pollutant, and thus it is a current area of concern. Oilseed rape (Brassica napus L.) is well known as a major source of edible oil around the globe. Due to its higher growth, larger biomass and capability to uptake toxic materials B. napus is considered a potential candidate plant against unfavorable conditions. To date, no study has been done that des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 70 publications
2
21
0
Order By: Relevance
“…Literature has evidenced that a non-enzymatic based antioxidant called GSH play a crucial role in scavenging the ROS, the photosynthesis by-products inside the cell organelles and also inactivates the singlet oxygen species with the help of ascorbate. Thus, GSH helps the plants to get recovery from negative effects of ROS on the plant's growth and development induced by hazardous environmental conditions (Mittler, 2002 ; Gill et al, 2016a ). Moreover, GSH-ascorbate cycle is well-unspoken to detoxify the singlet oxygen species i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature has evidenced that a non-enzymatic based antioxidant called GSH play a crucial role in scavenging the ROS, the photosynthesis by-products inside the cell organelles and also inactivates the singlet oxygen species with the help of ascorbate. Thus, GSH helps the plants to get recovery from negative effects of ROS on the plant's growth and development induced by hazardous environmental conditions (Mittler, 2002 ; Gill et al, 2016a ). Moreover, GSH-ascorbate cycle is well-unspoken to detoxify the singlet oxygen species i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The unique nature of the thiol group helps to stabilize mercaptide–metal bonds. This type of stable bond formation in conjunction with higher water solubility presents GSH as a better scavenger against the toxicity of multiple metals (Gill et al, 2016a ; Zlobin et al, 2017 ), reactive oxygen species (ROS) (Gill et al, 2014 , 2015 , 2016b ), and other hazardous chemicals (Barrameda-Medina et al, 2017 ; Li et al, 2017 ). Previous reports have indicated that GSH plays a vital role in regulating the levels of oxygen singlet species (such as H 2 O 2 ) that can be induced by heavy metal stress in plant cells (Shao et al, 2008 ; Gill et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was first extracted and mixed with DNase I to avoid DNA contamination Gill et al [ 65 ]. The oligo (dT) magnetic beads were used to enrich mRNA, and cDNA was synthesized by the fragments of mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Cr transport promotes gaps in other types of nutrient absorption and water [3]. Most studies on Cr-plant interactions have addressed Cr transfer from soil to plant and Cr hyperaccumulation for phytoremediation purposes (e.g., [4]) and morphophysiological and biochemical responses (e.g., root surface area, growth, morphology, photosynthesis, water/nutrient interactions, and transpiration) (e.g., [1,5]). Cr accumulation promotes an impairment of photosynthesis in the chloroplasts [3]; thus, these effects promoted a reduction of plant biomass [6].…”
Section: Introductionmentioning
confidence: 99%